Cyclic transition of deformation in {1 2 3}<6 3 4> single crystal processed by accumulative roll-bonding. Issue 18 (12th December 2019) - Wang, Hui; Lu, Cheng; Tieu, Kiet
ABSTRACT: In this study, the crystal plasticity finite element method model was used to study the deformation in a single crystal aluminium processed by accumulative roll-bonding (ARB). The predicted textures match well with the experimental observations up to nine cycles. The texture and slip activities in representative layers were investigated, and cyclic transition of them was observed. It was found that the thickness position change caused by cutting and stacking was a basic reason for the cyclic transition. Finally,  the effect of shear deformation to this transition was discussed.